The impact of chronic liver disease in patients receiving active pharmacological therapy for opioid use disorder: One-year findings from a prospective cohort study. (1st April 2020) - Dennis, Brittany B.; Akhtar, Daud; Cholankeril, George; Kim, Donghee; Sanger, Nitika; Hillmer, Alannah; Chawar, Caroul; D'Elia, Alessia; Panesar, Balpreet; Worster, Andrew; Marsh, David C.; Thabane, Lehana; et al.
Highlights: Despite effective therapies, the incidence opioid-related overdose, and its associated mortality continues to rise at an alarming rate. The impact of comorbid features such as chronic liver disease (CLD) on methadone treatment response remain unclear. The presented work details results from the largest cohort study to date, establishing CLD was associated with a higher burden of addiction severity. Increased levels of emotional stress, unemployment, domestic conflict, physical comorbidity, and opioid craving were observed in CLD patients. Closer monitoring, substance abuse contracting with contingency management strategies should be considered to reduce mortality risk for these patients. Abstract: Introduction: Despite the demonstrated benefit of methadone, the incidence opioid-related overdose, and its associated mortality continues to rise at an alarming rate. The impact of high prevalence comorbid features such as chronic liver disease (CLD) on methadone treatment response remain unclear. Aim: To determine whether CLD is associated with poor response to methadone treatment. Methods: Using a well-established multi-center cohort from the Genetics of Opioid Addiction Study (GENOA), we evaluated if presence of CLD among 1234 eligible patients with opioid use disorder receiving methadone treatment impacted health and behavioural responses to treatment. CLD was classified as any liver disorder/dysfunction present for a minimum period of six months. Serial urine toxicology assessments were used to determine treatment response. The effect of CLD was determined using a multi-variable logistic regression model. Results: CLD was present in 25 % (n = 314) of the population. On average, patients with CLD were found to be older (mean age 44 vs 36 years, p < 0.0001), unemployed (81.8 % vs 61 %, p < 0.0001), and receiving government disability benefits at significantly higher rates (21.9 % vs 11 %, p < 0.0001). Increased levels of physical craving, emotional stress, as well as health risk behaviors were noted in CLD patients. Findings from the multi-variable model demonstrate a 68 % increased risk for dangerous opioid consumption behaviors (Odds Ration [OR]: 1.68, 95 % Confidence Interval [CI] 1.22, 2.31, p = 0.001) among patients with CLD. Methadone dose (OR: 0.76, 95 % CI 0.70, 0.81, p < 0.0001) was shown to be protective with a significant risk reduction of 24 % per 20 mg increase in methadone. Duration in treatment was also found to be protective (OR: 0.99, 95 % CI 0.97, 0.99, p < 0.0001). Conclusion: CLD poses a distinct risk for patients with opioid addiction. Closer drug monitoring, and substance use contingency management should be considered to reduce mortality risk in these patients.